Cost-Effectiveness of Aprepitant in Preventing Chemotherapy-Induced Nausea and Vomiting: A Systematic Review of Published Articles - Qiu, Tingting; Men, Peng; Sun, Tong; Zhai, Suodi (Frontiers in Public Health, 2021)
Objectives: The aim of this systematic review is to assess the published cost-effectiveness analyses of aprepitant for patients with chemotherapy-induced nausea and vomiting (CINV). Methods: A systematic literature search was performed on PubMed, EMbase, the Cochrane Library, CNKI, WANFANG DATA, and CBM database. The date of publication is up to January 2019. Two reviewers independently reviewed titles, abstracts, and articles sequentially to select studies for data abstraction based on the inclusion and exclusion criteria. Disagreements were resolved and reviewers reached a consensus. The quality of the included studies was assessed according to the 24-item checklist of the consolidated health economic evaluation reporting standards (CHEERS). The costs reported by the included studies were converted to US dollars via purchasing power parities (PPP) in the year 2019 using the CCEMG–EPPI–Certer Cost Converter. Results: Thirteen articles were included based on the inclusion criteria for cost-effectiveness analysis and cost-utility analysis. Twelve studies were rated as good quality and one as a moderate quality based on the CHEERS checklist. Eight studies compared aprepitant plus 5-hydroxytryptamine-3 receptor antagonist (5-HT3RA) and dexamethasone with the standard regimen (5-HT3RA and dexamethasone). It was concluded that aprepitant plus standard regimen was a cost-effective strategy for preventing CINV. Only one study that compared aprepitant plus 5-HT3RA with 5-HT3RA, concluded that the addition of aprepitant reduced the incidence of severe nausea, and it might also provide an economic benefit in the overall management. Four studies that compared aprepitant with other antiemetic drugs concluded that aprepitant is a cost-effective strategy for preventing CINV compared with metoclopramide. However, netupitan + palonosetron and olanzapine are cost-effective compared with aprepitant. Conclusion: This study is the first systematic evaluation of adding aprepitant to standard regimens for patients with CINV. Most economic evaluations of antiemetic medications are reported to be of good quality. Adding aprepitant to standard regimens is found to be a cost-effective strategy for preventing CINV.